SOSIALISASI EKONOMI SIRKULAR SEBAGAI BAGIAN DARI EKONOMI HIJAU DI DESA BAWAHAN PASAR KECAMATAN MATARAMAN KABUPATEN BANJAR - Malihah, Lola; Karimah, Husna; Musfida Afif, Ahmad; Syarif Hidayatullah, Muhammad (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2024)
Waste as a waste material from human consumption activities is inevitable. The amount of waste that continues to increase every year has caused many changes to the environment, especially unmanaged plastic waste. This Community Service activity aims to socialize economic potential through the use of household waste, especially those made from plastic. The target of this activity is housewives in Subordinate Market Village. Some things to consider include: housewives carrying out daily activities are always related to household waste, and a lot of household waste is not managed because there is no waste bank in the village. Through this socialization activity, it is hoped that housewives can utilize their household waste by making it into handicraft items that have economic value. But if it is not possible, they can do a simple thing by sorting wet and dry waste, so that household waste from plastic can be deposited into the waste bank or sold to scavengers. So that the amount of waste that is not kola can be reduced and environmental improvement efforts can be implemented. After this activity, the plastic waste management system was carried out by teachers in the local village's Early Childhood Education (PAUD), where mothers in this village were allowed to torture their waste.  Keywords: Circular economic, Green economics, Garbage,